Effect of Temperature and Capping Agents on Structural and Optical Properties of Tin Sulphide Nanocrystals. (2nd January 2019) - Oluwalana, Abimbola E.; Ajibade, Peter A.
Abstract : SnS nanocrystals were synthesized using bis(phenylpiperazine dithiocarbamate)tin(II) in oleic acid (OA) and octadecylamine (ODA) at three different temperatures (150, 190, and 230°C). XRD diffraction pattern confirms that OASnS and ODASnS nanoparticles are in the orthorhombic phase and the type of capping agent used affects the crystallinity. Transmission electron microscopy (TEM) images shows spherically shaped nanocrystals for oleic acid capped SnS (OASnS) while octadecylamine (ODASnS) are cubic. Monodispersed SnS of size range 10.67–17.74 nm was obtained at 150°C for OASnS while the biggest-sized nanocrystals were obtained at 230°C for ODASnS. Temperature and capping agents tuned the crystallite sizes and shapes of the as-prepared nanocrystals. Electron dispersive X-ray spectroscopy indicates the formation of tin sulphide with the presence of Sn and S peaks in the nanocrystals. Flowery and agglomerated spherical-like morphology were observed for ODASnS and OASnS nanocrystals, respectively, using a SEM (scanning electron microscope). Direct electronic band gaps of the synthesized SnS nanocrystals are 1.71–1.95 eV and 1.93–2.81 eV for OASnS and ODASnS nanocrystals, respectively.